Financial development, homeownership and inequality - Vale, S.; Camões, F. (86th International Atlantic Economic Conference, 2018)
Throughout the past decades, the financial system experienced a worldwide unprecedented development, marked by an increased participation of households in the credit market. Sideways with a sustained increase in house prices, credit to the private sector surged at a substantial pace driven by the appeal of homeownership and the easing of mortgage contracts. Alongside, as the residential property seemed to become more democratic outspreading to fringes of the population that used to be credit constrained, inequality surged driven by the striking increase of top incomes (Piketty, 2014; Piketty and Zucman, 2014; Milanovic, 2016). The synchronization of these developments suggest that the extension of the financial sector to households may have increased their exposure to credit booms and busts and widened the gap between the poorer and the richer. This paper studies the relationship between households increased participation in the financial market as homeowners and the progress of inequality in several advanced and emerging economies from the late 1980s. Inequality is captured by the Gini coefficient, distinguishing market inequality from after-tax inequality, both regressed against two measures of household participation in the financial market, the ratio of private credit to GDP and an index of house prices. To control for other drivers of unequal income distribution the estimations take into account variables that try to capture recent trends such as globalization, or unemployment, while consider generic features of its populations as the education level and the fertility ratio. The empirical analysis relies on panel data models that control for country fixed effects. The findings point to private credit as a percentage of GDP contributing to increase inequality while the evolution of house prices tending to decrease it. These results are robust to different measures of inequality, financial development, and control variables.